The Role of Rituals and Ceremonies in the Identity Struggle of a Society that Has Lost Its Language: the Example of Lithuanian Tatars - Aça, Mehmet (Lietuvos istorijos studijos, 2023)
Language, history, geography, belief, and culture have an important role in the societies to have a common identity and to maintain their existence by embracing this identity. Identity generally refers to a person or group’s defini tion of itself and its positioning among other people or groups. One of the basic processes of the formation of identities at the group level is collective memory. A common emphasis plays an important role in the formation of group identi ty. Rituals and ceremonies are very functional in highlighting a common past and keeping the collective memory alive. Ritual, which means the repetition of certain values related to individuals or groups with symbolic and invariable sequential behaviour patterns, is an emotional channel that feeds group con sciousness and  unity.  It guides new  knowledge  and experience.  Rituals  that connect the past to the present and the present to the future can be either reli gious or secular. Rituals contribute to the raising of group consciousness in the participants; they determine social status and roles; they offer ready patterns of behaviour by showing how the individual will behave in society; they connect individuals to the past with an emotional bond.Lithuanian Tatars, who had important rights and privileges recognized by the Grand Duchy of Lithuania as the equivalent of their important services, have preserved their identity thanks to the rights and privileges granted to them, Islamic beliefs, rituals and ceremonies. Religious rituals, commemoration and celebration ceremonies supported the efforts of Lithuanian Tatars to keep their traditions alive; contributed to efforts to maintain ties between them; it kept their commitment to the roots or the common past alive. Celebrations and ceremonies related to religious festivals and transition periods perform im portant duties in the transfer of culture to children and young people. The celebration and commemoration programs organized for the 620th anniver sary of the arrival of the Tatars in the Grand Duchy of Lithuania, on the one hand, expressed loyalty to the Lithuanian State and the Lithuanian people, on the other hand, contributed to remembering the roots. In particular, Sabantuy, held in Lithuania in 2017, contributed to the development of the relations of Lithuanian Tatars with other Tatar groups living in the Russian Federation and Anatolian Turks.In this study, rituals and ceremonies will be discussed and interpreted through various rituals (religious festivals, rites of passage, Sabantuy, etc.) and ceremonies that contribute to the efforts of the Lithuanian Tatars to protect their identity and culture.
Keywords: loss of language; Lithuanian Tatars; identity; collective memory; ritual; ceremony